Pendugaan Cadangan Karbon Taman Hutan Raya Pocut Meurah Intan Provinsi Aceh - Ismed Ramadhan; Hairul Basri; Fauzi Harun (Program Studi Magister Konservasi Sumberdaya Lahan, Pascasarjana, Universitas Syiah Kuala, 2014)
Abstract : The objective of this study was to assess the amount of carbon stock stored in the Forest Park Pocut Meurah Intan, and carbon stocks in each vegetation type in a total area of 6.044 Ha research. The experiment was conducted for 6 (six) months. The study used descriptive method with a sample line system. Variables were carbon stored in the above ground and below ground biomass that consisted of plants, roots, nekromass form of litter and dead wood and total soil carbon. Spatial analysis using ArcGIS 9.1 software and laboratory analysis of soil samples was conducted at Syiah Kuala University of Faculty of Agriculture using the method incineration. The results showed that the amount of carbon stock of forest parks Pocut Meurah Intan was 657.296,6 ton, which was originated from the primary forest of 469.576,4 ton, Pine Forest of 71.289,4 ton, Mixed Farms of 97.890 ton, shrub vegetation of 14.811,2 ton and Banana gardens of 3.729,6 ton. In population of vegetation types, the higher numbers of tree which have the greater of diameter (dbh), the greater of carbon stocks will be founded. Abstrak : Penelitian ini bertujuan untuk mengetahui cadangan karbon pada setiap tipe vegetasi dan total karbon pada Taman Hutan Raya Pocut Meurah Intan dengan luas objek penelitian 6.044 Ha. Penelitian dilaksanakan selama 6 (enam) bulan. Penelitian ini menggunakan metode deskriptif dengan teknik penarikan contoh sistem Jalur. Peubah yang diamati adalah kantong karbon tersimpan pada tanaman atas, tumbuhan bawah, akar, nekromasa berupa serasah dan kayu mati serta total karbon tanah. Analisa spasial menggunakan software ArcGIS 9.1 dan analisa sampel dilakukan di laboratorium tanah Fakultas Pertanian Universitas Syiah Kuala dengan menggunakan metode pengabuan. Hasil penelitian menunjukkan bahwa diduga jumlah cadangan karbon taman hutan raya Pocut Meurah Intan sebesar 1,272,488 ton, yang berasal dari vegetasi Hutan Primer 469.576,4 ton, Hutan Pinus 71.289,4 ton, Kebun Campuran 97.890 ton, Semak Belukar 14.811,2 ton dan Kebun Pisang 3.729,6 ton. Besarnya cadangan karbon pada suatu tipe vegetasi dipengaruhi oleh tingginya populasi jumlah pohon yang memiliki diameter (lingkar batang) yang besar.